Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.1007/s00018-010-0379-6
|View full text |Cite
|
Sign up to set email alerts
|

Bimodal expression of Sprouty2 during the cell cycle is mediated by phase-specific Ras/MAPK and c-Cbl activities

Abstract: Sprouty2 is an important inhibitor of cell proliferation and signal transduction. In this study, we found a bimodal expression of Sprouty2 protein during cell cycle progression after exit from quiescence, whereas elevated Sprouty4 expression in the G1 phase stayed high throughout the rest of the cell cycle. Induction of the mitogen-activated protein kinase via activated Ras was crucial for increased Sprouty2 expression at the G0/G1 transition. Following the first peak, accelerated proteasomal protein degradati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 49 publications
1
12
0
Order By: Relevance
“…Thus, Spry2 accumulates to higher levels and inhibits FGF-induced signaling more efficiently in c-Cbl-null mouse embryonic fibroblasts (MEFs) than in control MEFs [89, 90]. Reporting bimodal expression of Spry2 along with sustained elevation of Spry4 during cell cycle progression, Mayer et al [91] indicated that second phase in the expression profile of Spry2 as transient attenuation of the protein expression during late G1 is solely dependent on cell cycle-specific ubiquitination by c-Cbl. DaSilva et al [92] showed that serine phosphorylation on Ser112 and Ser121 by MAPK-interacting kinase 1 (Mnk1) provides Spry2 with balanced phosphorylation of Tyr55 that leads to the protein stabilization.…”
Section: Sprouty: a Versatile Modulator With Complex Functionalitymentioning
confidence: 99%
“…Thus, Spry2 accumulates to higher levels and inhibits FGF-induced signaling more efficiently in c-Cbl-null mouse embryonic fibroblasts (MEFs) than in control MEFs [89, 90]. Reporting bimodal expression of Spry2 along with sustained elevation of Spry4 during cell cycle progression, Mayer et al [91] indicated that second phase in the expression profile of Spry2 as transient attenuation of the protein expression during late G1 is solely dependent on cell cycle-specific ubiquitination by c-Cbl. DaSilva et al [92] showed that serine phosphorylation on Ser112 and Ser121 by MAPK-interacting kinase 1 (Mnk1) provides Spry2 with balanced phosphorylation of Tyr55 that leads to the protein stabilization.…”
Section: Sprouty: a Versatile Modulator With Complex Functionalitymentioning
confidence: 99%
“…Synchronization of cells in certain phases of the cell cycle was achieved by serum starvation as described (21). Propidium iodide-based DNA content analysis (PI-staining) was performed as described (22).…”
Section: Methodsmentioning
confidence: 99%
“…Western blotting was performed as described (21). Primary antibodies against β-actin (Novus Biologicals, CO, USA) and Au5 epitope (Bethyl Laboratories, TX, USA) were used.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…17 Also, Spry4 expression can be induced when cells are stimulated by the activation of RTK-mediated signaling via addition of epidermal growth factor (EGF), FGF2, serum or RAS expression. 15,16 Although at mRNA level, two reports describe a reduction of Spry1 levels 13,14 , whereas in another experiment, Spry1 mRNA is induced in response to growth factor addition, 18 Spry1 protein in response to growth factor activation was not investigated. The goal of this study is to examine the influence of RTK-signaling on Spry1 protein expression in tumor and normal cells of the lung.…”
Section: Introductionmentioning
confidence: 92%